CGIAR System Annual Performance Report 2018: Summarized Report - CGIAR System Organization (CGIAR System Organization, 2019)
Agriculture is at the heart of both the problems and solutions that link nutrition to climatic and environmental change. The immense challenges demand novel solutions, putting research for development at the center of shared agendas for action and transformation.